Fault diagnosis of rolling bearing of wind turbines based on the Variational Mode Decomposition and Deep Convolutional Neural Networks - Xu, Zifei; Li, Chun; Yang, Yang (Applied soft computing, 2020)
Machine learning techniques have been successfully applied in intelligent fault diagnosis of rolling bearings in recent years. However, in the real world industrial application, the dissimilarity of data due to changes in the working conditions and data acquisition environment often cause a poor performance of the existing fault diagnosis methods. Consequently, to address these inadequacies, this paper developed a novel method by integrating the Convolutional Neural Networks (CNNs) with the Variational Mode Decomposition (VMD) algorithms. Named as “Variational Mode Decomposition with Deep Convolutional Neural Networks (VMD-DCNNs)”, the method, in an end-to-end way, directly processes raw vibration signals without artificial experiences and manual intervention to realize the fault diagnosis of rolling bearings. In addition, the CNN technique is used to extract features from each Intrinsic Mode Function (IMF) in order to address the deficiency in extracting features from a single source and to achieve an effective and efficient fault diagnosis of rolling bearings under different environments and states. The value of parameter K of the VMD-DCNNs model is optimized by considering time complexity and generalization ability of the model. Lastly, bearing experiments are conducted to verify the superiority of the VMD-DCNNs in diagnosing fault under different conditions. The visualizations of the signals in the convolutional layer explain the reasonability in selecting the value of parameter K and they also indicate that the translational invariances in a raw IMF component have been learned by the VMD-DCNNs model. •A novel fault diagnosis method is developed by integrating the Convolutional Neural Networks (CNNs) with the Variational Mode Decomposition (VMD) algorithms.•The proposed VMD-DCNNs method directly works on raw vibration signals.•The proposed VMD-DCNNs method has a good extrapolation performance under different scenarios.•Different IMF mode generated by VMD has a similar translation invariances learning by VMD-DCNNs model.